THE STORY OF TWO NORTHWARD MIGRATIONSORIGINS OF FINNO-PERMIC AND BALTO-SLAVIC LANGUAGES IN NORTHEAST EUROPE, BASED ON HUMAN Y-CHROMOSOME HAPLOGROUPS337 - Horváth, Csaba Barnabás (European Scientific Journal, ESJ, 2014)
This paper attemps to find a plausible explanation for the origins of Balto-Slavic and Finno-Permian languages in Northeast Europe by a research based on the analysis of statistical databases of human Y-chromosome haplogroups . The mainstream view that associates Balto-Slavic languages with haplogroup R1a and íthe Corded Ware Culture, and Finno-Permian languages with haplogroup N, fails to solve several contradictions: How come, that the presence of subclades of haplogroup R are as high in most Finno-Permian populations, as the presence of haplogroup N? How come, that Corded Ware culture spread so far north, that it covered the early-medieval range of most Finno-Permic languages? This paper is trying to set up a hypothesis that solves these contradictions.